(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the treatment status of HIV patients with Lamivudine, Tenofovir, and Dolutegravir at Long An General Hospital. Subjects and methods: Retrospectively describe over 80 HIV/AIDS-infected patients being treated with a 3-drug regimen using Lamivudine 300mg, Tenofovir 300mg, Dolutegravir 50mg of inpatient and outpatient treatment at the Department of Infectious Diseases, Long An General Hospital. Results: Male patients accounted for the majority (58.8%); average age was 34.3 ± 7.1 years old. The majority of patients started at stages 1 and 2 (62.6%) and maintained during treatment. Regarding the immune stage, the majority of patients treated at the stage of significant and severe immunodeficiency accounted for 26.3% and 28.8%, respectively. There were 100.0% of patients started treatment with TDF/3TC/DTG regimen (Acriptega). Conclusion: The majority of patients began in stages 1 and 2. The majority of patients were treated at the stage of significant and severe immunodeficiency. Patients started treatment with TDF/3TC/ DTG regimen (Acriptega).